(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Singh AK, Kumar S, Jyoti B. 2022. Influence of climate change on agricultural sustainability in India: A State-wise panel data analysis. Asian J Agric 6: 15-27. This study developed Economic Efficiency Index (EEI), Social Equity Index (SEI), and Ecological Security Index (ESI) as an assessment of the Agricultural Sustainability Index (ASI) in 17 Indian states during 1990-2017. The Composite Z-Score method integrated 32 economic, social, and ecological security factors to create ASI, EEI, SEI, and ESI. Subsequently, it examined the impact of climatic factors on ASI using linear, log-linear, and non-linear regression models through state-wise panel data during the said period. The descriptive results indicate that agricultural sustainability was positively associated with economic efficiency, social equity, and ecological security. Therefore, factors related to economic efficiency, social equity, and ecological security would help improve sustainability in the Indian agricultural sector. Furthermore, there was high diversity in economic efficiency, social equity, and ecological security across the Indian state. The ratio of agriculture’s Gross Domestic Product (GDP) and gross irrigated area with the gross sown area, landholding size, yield of food-grain and oilseed crops, and cropped area under food-grain crops were observed to be the most influencing factors of economic efficiency. The total literacy rate, female literacy rate, and rural literate population were the most crucial factors in improving social equity. Ecological security was improved with increased forest area, pastureland, and cropping intensity. Furthermore, the empirical results also showed that maximum temperature had a negative influence; and economic efficiency, social equity, and ecological security positively influenced agricultural sustainability in India. Therefore, India needs to take effective climate policy action to mitigate the negative impact of climate change in the agricultural sector and its allied activities to increase sustainable agricultural development in India. Subsequently, this study provided several policy suggestions to reduce climate change risk in the Indian agricultural sector.